Parents’ involvement in their children’s education during the pandemic - Rodriguez Medina, Valeria Cristina (2023)
The participation of parents in the education of their children is an important aspect for academic progress, however, during the time of confinement due to the COVID-19 pandemic, there has been little information on the involvement of the family in children’s education. Therefore, the study is carried out whose main objective is to systematize the information published to date in different databases: Scopus, Scielo, Dialnet and REDIB, etc. For the search for information, keywords were used, such as “participation of parents in education” “parents and their educational function” “role of parents in education” “parental participation in education” “education, family, and COVID-19”. The results show that there are few works that account for the participation of parents in their children’s education even though it is a very important aspect for social, cultural, emotional, and affective development, which is directly related to academic success. Therefore, based on the reviewed literature, it is concluded that the educational role of parents contributes to the integral development of the child and generates emotional, physical, and cognitive well-being in them, for which it is necessary to promote research that continues to deepen, from different perspectives, this involvement of the family to improve the academic achievements of schoolchildren.